2D Ferroelectrics: Enhanced Spontaneous Polarization in Ultrathin SnTe Films with Layered Antipolar Structure (Adv. Mater. 3/2019). Issue 3 (15th January 2019) - Chang, Kai; Kaloni, Thaneshwor P.; Lin, Haicheng; Bedoya‐Pinto, Amilcar; Pandeya, Avanindra K.; Kostanovskiy, Ilya; Zhao, Kun; Zhong, Yong; Hu, Xiaopeng; Xue, Qi‐Kun; Chen, Xi; Ji, Shuai‐Hua; et al.
Abstract : The underlying mechanism of the transition temperature in ferroelectric 2D SnTe films with a thickness of as little as 2 atomic layers is determined by Stuart S. P. Parkin and co‐workers, as described in article number1804428 . The observed high transition temperature, together with the strong spin‐orbit coupling and van der Waals structure, underlines the potential of atomically thin γ‐SnTe films for the development of novel spontaneous‐polarization‐based devices.